2021
DOI: 10.1089/dia.2020.0234
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Virtual Training on the MiniMed™ 670G System in People with Type 1 Diabetes During the COVID-19 Pandemic

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has challenged the ability to do face-to-face training on advanced diabetes management technologies. In the United States, Medtronic Diabetes shifted from occasional to 100% virtual training on all diabetes devices in mid-March 2020. We studied the outcomes of virtual training on the MiniMed™ 670 G hybrid closed-loop system in type 1 diabetes. Methods: From March 20, 2020, to April 22, 2020 (intra-COVID-19), v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 1 publication
5
48
0
Order By: Relevance
“…Studies of adolescents and adults have shown improvements in HbA1c and time in range 9 . As suggested by some providers in our study, other researchers attributed improvements in glycemic control during COVID‐19 to more parental presence, meals at home, and a more consistent eating pattern 9‐11 …”
Section: Discussionsupporting
confidence: 74%
“…Studies of adolescents and adults have shown improvements in HbA1c and time in range 9 . As suggested by some providers in our study, other researchers attributed improvements in glycemic control during COVID‐19 to more parental presence, meals at home, and a more consistent eating pattern 9‐11 …”
Section: Discussionsupporting
confidence: 74%
“…The spread of COVID 19 has challenged health care systems from all the world [ 5 ]. Given the current contingency, studies consider that the use of teleconsultation has increased by 80% during 2020 [ 6 ]. Therefore, it was necessary to design and evaluate an educational program through virtual platforms for patients planning to start HCL therapy that complies with government regulations [ 7 ] and allows frequent follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Vikersky reported Glycemic outcomes data from CareLink™ Personal database from patients who were new to using the MiniMed™ 670 G system during the pre-COVID-19 and the intra-COVID-19 eras. He did not reported the number of patients evaluated, nor the basal TIR in previous therapy, however he found that the TIR was similar in both periods (70.4 vs 68.4%), suggesting than virtual training of individuals results comparable with in-person training [ 6 ]. Our data are consistent with this conclusion, suggesting than the outcomes are at least similar to those reported for face-to-face training.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, diabetes technology companies are documenting the successful provision of remote device trainings to people who are transitioning to or need support using their products. 14 However, creating a robust and effective telehealth system that is also equitable remains challenging. This is often because of the impact of external factors and the ripple effect of other intractable societal problems.…”
Section: Telehealth Is Having a Good Pandemicmentioning
confidence: 99%
“…12 In addition, diabetes technology companies are documenting the successful provision of remote device trainings to people who are transitioning to or need support using their products. 14…”
Section: Telehealth Is Having a Good Pandemicmentioning
confidence: 99%